2021
DOI: 10.1016/j.jogn.2021.08.096
|View full text |Cite
|
Sign up to set email alerts
|

Roles and Experiences of Registered Nurses on Labor and Delivery Units in the United States During the COVID-19 Pandemic

Abstract: Objective To examine the roles and experiences of labor and delivery (LD) nurses during the COVID-19 pandemic. Design Cross-sectional survey. Setting Online distribution between the beginning of July and end of August 2020 Participants Labor and delivery nurses (N = 757) responded to an open-ended question about changes to their roles during the COVID-19 pandemic as part of a larger national survey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
65
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 28 publications
6
65
1
Order By: Relevance
“…Moderate stress has a motivational effect and promotes resilience, enabling nurses to cope with work-life challenges (22). Conversely, excessive stress could negatively impact patient safety, job satisfaction, environmental adaptation (the process by which the individual balances with the environment), performance, burnout, career development, physical and mental health, and turnover intention (23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…Moderate stress has a motivational effect and promotes resilience, enabling nurses to cope with work-life challenges (22). Conversely, excessive stress could negatively impact patient safety, job satisfaction, environmental adaptation (the process by which the individual balances with the environment), performance, burnout, career development, physical and mental health, and turnover intention (23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…Nurses faced an increased workload during the pandemic, not only related to the increased care needs, but also due to the continuous need to integrate and help new colleagues [ 15 ]. Some authors confirmed that integration times were reduced and that newly integrated professionals ended up verbalising a major dissatisfaction regarding the institutional policy for professional qualification [ 29 , 30 ]. In addition, nurses who were transferred to other services and had to integrate new teams that were unaware of their professional qualifications and often had no conditions to collaborate in their integration also felt a loss of control [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors confirmed that integration times were reduced and that newly integrated professionals ended up verbalising a major dissatisfaction regarding the institutional policy for professional qualification [ 29 , 30 ]. In addition, nurses who were transferred to other services and had to integrate new teams that were unaware of their professional qualifications and often had no conditions to collaborate in their integration also felt a loss of control [ 29 , 30 ]. In relation to the mentioned, authors recall that “more hands” are not always the best answer, particularly when competence and training are lacking [ 15 ], which reinforces once again the need to maintain professional qualification strategies [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed that the roles of nurses were directed toward preventing COVID-19 transmission and treating patients with or suspected of COVID-19, which affects the levels of work stress and staffing level [34]. A national US cross-sectional study that investigated the practice of labor and delivery nurses during the COVID-19 pandemic showed changes in the roles and responsibilities of nurses, as reported by half of the participants who perceived the effects of quality of patient care [35].…”
Section: Introductionmentioning
confidence: 98%